(untitled) (Bangladesh Journal of Botany, 2024)
Anticandidal activities of stem extracts of C. gileadensis growing in various locations and chemicals had been evaluated. Methanol extract of fresh and dry solvent extracts in Tathleeth A region had the highest activity (2.2 ± 0.3cm) and (1.7 ± 0.2cm), respectively. Cyclohexanone of fresh stem extract and diethyl ether of dry extract showed inhibition activities (2.1 ± 0.1cm) of Tathleeth B. The highest activity gained from fresh hot water extract (1.4 ± 0.1 cm) and from dry extract of dichloromethane (1.7 ± 0.0 cm) in Tabala C. The maximum inhibiting activity obtained from hot water extract (1.8 ± 0.4 cm) and from chloroform of dry extract (2.0 ± 0.0cm) in Tabala D. GC-MS analysis showed that the dominant compound in Thathleeth A and Thathleeth B is Bisethylamine, Tabala C are 5-Methyl-2(5H)-furanone and palmatic acid and Tabala D is Amitrole. HPLC showed that Tabala D had the highest amount from B1 and folic acid. Thus, plant’s biochemical parameters are profoundly influenced by their locations. Bangladesh J. Bot. 53(1): 1-8, 2024 (March)